Safety and Tolerability of Levomilnacipran ER in Major Depressive Disorder: Results from an Open-Label, 48-Week Extension Study - Mago, Rajnish (Springer International Publishing, 2013)
BACKGROUND: Levomilnacipran (1S, 2R-milnacipran) is a potent and selective serotonin (5-HT) and norepinephrine (noradrenaline) reuptake inhibitor approved for the treatment of major depressive disorder in adults. OBJECTIVE: The objective of this study was to evaluate the longer-term safety and tolerability of levomilnacipran extended-release (ER). METHODS: Patients who completed double-blind treatment/down-taper in one of three lead-in levomilnacipran ER studies were eligible for this 48-week open-label extension. Safety evaluations included assessment of treatment-emergent adverse events (TEAEs), physical examinations, laboratory and vital sign measures, and suicidality, summarized using descriptive statistics for the safety population. RESULTS: The completion rate was 47 %; median treatment duration was 280 days. The most frequent reasons for discontinuation were withdrawal of consent (14 %) and adverse events (AEs; 13 %). TEAEs were reported by 712 (86 %) patients; most were mild/moderate and occurred early in treatment. The most common TEAEs were headache (22 %) and nausea (16 %); 36 (4 %) patients had ≥1 serious AEs. No clinically meaningful changes occurred in mean liver enzyme, metabolic, hematologic, urinalysis, or serum values; potentially clinically significant high AST or ALT values (≥3 × upper limit of normal) occurred in five patients. Vital sign changes occurred early and remained relatively stable. Mean increases for pulse rate (9.1 beats per minute [bpm]), and supine systolic (3.9 mmHg) and diastolic (3.3 mmHg) blood pressure were noted. The increase in the mean QT interval corrected using the Bazett formula (10.9 ms) was consistent with heart rate increase (12.8 bpm); there was no meaningful change in mean QT interval corrected using the Fridericia formula (−1.3 ms). Other than tachycardia and heart rate increases, ECG-related TEAEs were low (<0.5 %). CONCLUSION: No new or inconsistent safety/tolerability findings were discovered during longer-term evaluation.